The Influence of Work Environment, Work Motivation, and Work Discipline on Employee Performance on CV Sido Hidup Makmur - Serly Aprilya Wati; Editya Nurdiana; Eteh Resa Asyifa (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to test and analyze the influence of work environment, work motivation, and work discipline on employee performance at CV Sido Hidup Makmur in Kuningan, West Java. Using a quantitative approach with the survey method, data was collected from 80 respondents through saturated sampling techniques (census) and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4 software. The results of the structural model analysis showed that the work environment had a positive and significant effect on employee performance with a path coefficient of 0.380. Work motivation was found to be the most dominant factor with the highest path coefficient of 0.441, indicating that intrinsic and extrinsic motivation are the main keys in driving productivity. Work discipline also makes a significant positive contribution with a coefficient of 0.242 in maintaining operational order. Simultaneously, the three variables have a strong predictive ability on employee performance with an R-square value of 0.732, which means that the model is able to explain 73.2% of the variation in performance in the company. This research concludes that the synergy between creating a conducive environment, increasing motivation, and consistent discipline enforcement is an effective strategy to optimize the performance of human resources in the manufacturing industry.